Evaluasi Kondisi dan Kerusakan Perkerasan Lentur Dengan Metode Pavement Condition Index (Pci) (Studi Kasus: Jalan Gunung Selatan Kota Tarakan Provinsi Kalimantan Utara) - Muhammad Djaya Bakri (Borneo Engineering : Jurnal Teknik Sipil, 2019)
The Gunung Selatan Road is a road of secondary collector with the class of road is IIIB, has a width of 6.0 meters and a length of 4.109 km, has an important role in driving the economy and connecting sub-districts in the north and west with sub-districts in the central and eastern parts of the city of Tarakan. The use of this road is directed to serve the transportation of construction materials which generally have a load to overloading which has the potential to cause damage to the road. This study aims to assess the condition of road pavement, using the method of the Pavement Conditition Index (PCI). Observation areas along the road segment are divided into road segments or sample units of observation with a width of 6.0 meters and a length of 50 m, so that the size of each segment of 300 m 2 is obtained, with a total of 40 road sample units. The types of damage found at the time of observation include: alligator crack, bleeding, block cracking, corrugation, depression, edge cracking, longitudinal/transverse cracking, patching and utility cut patching, pothole, and weathering/raveling. The average assessment results show the road is in criteria is very good condition with a value of PCI = 71, but there is one observation that gives a criteria is poor, namely the sample unit at Sta. 1 + 350 to 1 + 400 with a PCI value of 29.5. This happened, at the time of observation the field condition was damaged and was being repaired.